2000
DOI: 10.3366/afr.2001.71.2.286
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Land Acquisition and Struggles Over Land in the ‘Communal’ Areas of Zimbabwe: The Gokwe Region in the 1980s and 1990s

Abstract: How do histories shape the way people map their present and envision the future, especially at a moment of rapid political, economic and social transformation like that associated with the shift from socialism to liberal market economy/polity in Tanzania? Is the past a`foreign land' (as Lowenthal argues) or are reproductions and traces of multiple temporalities constitutive of the present and the possibilities for the future? In this article I explore how different moments and aspects of the past in the sisal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…With regard to the referencing of interviews, Nyambara (2001a: 266) notes an unwillingness of informants to provide full information about cash transactions in land, and in my own research a reticence and fear of reprisals was evident, and information generally only vouchsafed following an assurance of confidentiality. This dovetailed with university ethics requirements, and consequently no names and no detailed locations are given in this article.…”
Section: Methods and Referencingmentioning
confidence: 86%
See 3 more Smart Citations
“…With regard to the referencing of interviews, Nyambara (2001a: 266) notes an unwillingness of informants to provide full information about cash transactions in land, and in my own research a reticence and fear of reprisals was evident, and information generally only vouchsafed following an assurance of confidentiality. This dovetailed with university ethics requirements, and consequently no names and no detailed locations are given in this article.…”
Section: Methods and Referencingmentioning
confidence: 86%
“…My research showed that the emerging land market in Zimbabwe's communal areas is insecure for a number of reasons, and that those buying land rights not only strategize to maintain access to land (Nyambara 2001a: 281) but also to secure their rights once acquired. Bolstering of land right security is achieved first by investing in interpersonal links (both with the living and the dead), and second by the pragmatic adaptation of land-related ceremonies and practices to suit contemporary contexts (including that of urban land with links to rural land) and contemporary beliefs (for example the Christianizing of ceremonies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is viewed as individualistic, rational, equally applied, written down, abstract, and has clear procedures (Griffiths 1986). State law has limited influence on land transactions in rural areas of Sub-Saharan Africa (Moore, 1986;WLSA, 1995;Andersson, 1999;Nyambara, 2001a;Whitehead and Tsikata, 2003).…”
Section: Communal Farming Areas and Legal Pluralismmentioning
confidence: 99%